Harvest scheduling of southern highbush blueberries (Vaccinium corymbosum L. interspecific hybrids) in a climate with moderate winter chilling - Swart, Philippus (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.